Lactobacillus plantarum in high methoxylated pectin-based encapsulation systems supports gut epithelial wound healing in vitro - Felipe Galvez-Jiron; Lucas de Freitas Pedrosa; Luis Silva Lagos; Xin Tang; Traudy Wandersleben; Rodrigo Navia; Stephan Drusch; Francisca Acevedo; Paul de Vos (Food Hydrocolloids for Health)
Wound healing and gut epithelial barrier regulation are crucial for intestinal homeostasis. Effective repair of gut epithelial wounds is crucial for re-establishing the mucosal barrier and resolving inflammation. Pectins, versatile polysaccharides in food, protect sensitive components, such as living bacteria, during gastrointestinal transit and support wound healing by promoting cell proliferation and migration.This study investigated the effects of encapsulated Lactobacillus plantarum WCFS1 on cell proliferation and migration during epithelial wound healing, using pectin-based beads stabilized with alginate or chitosan. Pectin from lemon, with two degrees of methyl esterification (DM18 and DM88), produced four microbead types. T84 cells were incubated with these beads for 24 hours. The results revealed that cell proliferation and migration were influenced by the bead type, the degree of methyl esterification of the pectin, and the inclusion of L. plantarum. Empty DM88 pectin beads improved cell proliferation while reducing migration tendencies, whereas DM18 beads delayed migration.Beads containing L. plantarum demonstrated different effects: DM18 beads enhanced proliferation without inhibiting migration, while DM88 beads reduced migration. Both empty and L. plantarum-loaded beads decreased CCL20 production. Alginate/pectin beads with L. plantarum increased IL-8, while chitosan/pectin beads delayed migration, reduced CCL20 secretion, and modulated IL-8 levels.In conclusion, DM88 pectin beads without L. plantarum and DM18 beads containing L. plantarum supported cell proliferation over migration during epithelial wound healing. These findings suggest that pectin-based encapsulation systems may play a role in promoting gut health, protecting barrier integrity, and delivering therapeutic agents.